Elastic buckling and load resistance of a single cross-arm pre-tensioned cable stayed buckling-restrained brace. (1st November 2016) - Guo, Yan-Lin; Fu, Peng-Peng; Zhou, Peng; Tong, Jing-Zhong
Highlights: A pre-tensioned cable stayed buckling-restrained brace (PCS-BRB) is proposed. PCS-BRB significantly improves the overall external restraining stiffness. Equilibrium method is utilised to deduce elastic buckling load of pin-ended PCS-BRB. PCS-BRB buckles spatially with the same axial load in arbitrary directions. Ultimate load-carrying capacity of PCS-BRB is directly proportional to restraining ratio. Abstract: This paper proposes a new type of buckling-restrained braces (BRB), namely a pre-tensioned cable stayed buckling-restrained brace (PCS-BRB) which is formed through introducing an additional structural system of pre-tensioned cables and a number of cross-arms to the outside of a common BRB. This new system significantly improves the BRB's overall external restraining stiffness, hence increasing the load-carrying efficiency in its structural design. Due to its aesthetically appealing structure, it can be utilised in stadiums and so forth as a laterally resistant brace. Equilibrium method is utilised to deduce formulas of elastic buckling load of pin-ended PCS-BRB. The restraining ratio and the initial pre-tensioning force of cables are investigated to explore the effect on the axial compressive load-carrying capacity of the PCS-BRB through finite element analyses in elastic-plastic range. The findings indicate that two different types of buckling modes may occur in this PCS-BRB, namely single-wave symmetric and double-wave antisymmetric buckling modes. It was found from theoretical and numerical analyses that: a negative linear correlation exists between elastic buckling load and initial pre-tensioning force of the cables; the geometric parameters of the cable stayed system possessed remarkable effect on the elastic buckling load. In addition, the post-yield behaviour and ultimate compressive load-carrying capacity of the PCS-BRB is directly proportional to the restraining ratio, and there exists a lower limit of the restraining ratio which allows the inner core to reach full cross-sectional yielding without overall instability failure of the PCS-BRB. Furthermore, there exists an optimal initial pre-tensioning force of cables to make the load-carrying capacity of the PCS-BRB to reach a maximum value. The investigation of elastic buckling and load resistance of PCS-BRB provides fundamentals to further develop a complete design method of PCS-BRB.